Enhanced tolerance of transgenic grapevines expressing chitinase and beta-1,3-glucanase genes to downy mildew - Nookaraju, Akula; Agrawal, Dinesh C. (Plant Cell Tissue and Organ Culture, 2012)
An Agrobacterium-mediated transformation protocol for grapevine cv. Crimson Seedless using sonication and anti-necrotic agents has been optimized, and transgenic lines carrying wheat chitinase and beta-1,3-glucanase genes have exhibited enhanced tolerance to downy mildew incited by Plasmopara viticola. cDNA clones encoding chitinase and beta-1,3-glucanase have been isolated from a cDNA library, constructed from scab-infected Sumai-3 wheat, and introduced into a plant cloning vector to generate the plasmids pCAMBAR.chi.11 and pCAMBAR.638. Embryogenic cultures, established from in vitro-derived leaves, of Crimson Seedless were used as explants for Agrobacterium tumefaciens-mediated transformation studies. Sonication of somatic embryos in a bacterial suspension of A. tumefaciens and incorporation of anti-necrotic agents in the co-cultivation medium significantly enhanced transformation efficiency. Transformation efficiency of embryos with either chitinase or beta-1,3-glucanase gene was highest when embryos were suspended in a bacterial cell suspension at 0.5 OD600 and sonicated for 2 or 3 s at 60 kHz. Transformation efficiency with chitinase was highest on incorporation of 2 or 3 mg l(-1) phenylalanine, 1 or 2 mg l(-1) silver nitrate or 400 mg l(-1) l-cysteine in co-cultivation medium while incorporation of 20 mg l(-1) sodium thiosulphate produced highest transformation efficiency with beta-1,3-glucanase. Confirmed transgenic grapevine lines harboring anti-fungal genes exhibited higher levels of chitinase and beta-1,3-glucanase transcripts as well as enzymatic activities. Moreover, transgenic lines showed enhanced tolerance to P. viticola infection following detached leaf assays.
Keywords: Agrobacterium tumefaciens; Anti-oxidants; Downy mildew tolerance; Grapevine; Sonication

Simple recovery of intracellular gold nanoparticles from peanut seedling roots - Raju, D.; Mehta, Urmil J.; Ahmad, Absar (Journal of Nanoscience and Nanotechnology, 2015)
Fabrication of inorganic nanomaterials via a biological route witnesses the formation either extracellularly, intracellulary or both. Whereas extracellular formation of these nanomaterials is cherished owing to their easy and economical extraction and purification processes; the intracellular formation of nanomaterials, due to the lack of a proper recovery protocol has always been dreaded, as the extraction processes used so far were tedious, costly, time consuming and often resulting in very low recovery. The aim of the present study was to overcome the problems related with the extraction and recovery of intracellularly synthesized inorganic nanoparticles, and to devise a method to increasing the output, the shape, size, composition and dispersal of nanoparticles is not altered. Water proved to be much better system as it provided well dispersed, stable gold nanoparticles and higher recovery. This is the first report, where intracellular nanoparticles have been recovered using a very cost-effective and eco-friendly approach.
Keywords: gold nanoparticles; Peanut; Recovery; Sonication; Water